HUBUNGAN ANTARA POLA ASUH PERMISIF DAN KONFORMITAS TEMAN SEBAYA DENGAN PERILAKU ALKOHOLIK PADA REMAJA DI DESA TIGAJURU KABUPATEN JEPARA - Ivan Firdaus; Fajar Kawuryan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to empirically determine the relationship between permissive parenting and peer conformity with alcoholic behavior in adolescents in Tigajuru village, Jepara Regency. This research is quantitative in nature. This research was conducted from July to December 2024. In this study, researchers took the population as adolescents in Tigajuru village, Jepara district aged 18-23 years who more than 2 years often consume liquor / alcohol. The sampling technique used in this study is non probability sampling with purposive sampling method. Data collection in this study used a permissive parenting scale consisting of 19 unfavorable items with a reliability of 0.963, a peer conformity scale consisting of 11 items divided into 2 favorable items and 9 unfavorable items with a reliability of 0.963, and an alcoholic behavior scale consisting of 11 items divided into 1 favorable item and 10 unfavorable items with a reliability of 0.963. Data analysis in this study used two predictor regression analysis methods and product moment. The results of this study show a p value of 0.506 (p.>0.05) so that the major hypothesis that says there is a significant relationship between permissive parenting and peer conformity with alcoholic behavior is rejected with an effective contribution of 0.34%. Thus, the conclusion of this study is that permissive parenting and peer conformity do not have a significant influence on alcoholic behavior in adolescents in Tigajuru village, Jepara Regency.